Adverse Effects Following Immunisation and Vaccine Hesitancy: A Qualitative Study in a South Indian District - Gopalan RB; Babu BV; Sarma S K; John RP (Drug, Healthcare and Patient Safety, 2025)
Retheesh Babu Gopalan,1 Bontha V Babu,2 Krishna Sarma S,1 Rooth P John1 1ICMR-National Institute of Virology, Kerala Unit, Alappuzha, 688 005, India; 2Division of Socio-Behavioural, Health Systems & Implementation Research, Indian Council of Medical Research, New Delhi, 110 029, IndiaCorrespondence: Bontha V Babu, Division of Socio-Behavioural, Health Systems & Implementation Research, Indian Council of Medical Research, New Delhi, 110 029, India, Tel -+91-11-26589277, Email babubontha@gmail.comBackground: Parental perceptions and concerns about vaccine safety and ‘adverse effects following immunisation’ (AEFI) are the reasons for vaccine hesitancy. This study aimed to understand how these vaccine-related concerns have become significant determinants of vaccine decision-making among non-vaccinating parents in the Alappuzha district of Kerala, India. The healthcare providers’ views in this regard are also reported.Methods: This is a qualitative study. In-depth interviews were conducted with informants from 110 households having non-immunised/partly-immunised children. In addition, 18 healthcare providers were interviewed. Thematic analysis using the reflective thematic method was carried out.Results: Parents reported incidences of minor events of AEFI and are hesitant to continue vaccination in circumstances when children need medical treatment. AEFI incidents within the family have seriously hampered the trust in vaccines. Parents have concerns about multiple vaccinations and have misconceptions about the content of vaccines. Other concerns that lead to hesitancy are vaccine-related infertility, polio infection after polio vaccination and autism due to vaccination. Healthcare providers reported that there were no serious incidents that needed hospitalisation. Health workers opined that informing parents about AEFIs and preparing them is better.Conclusion: The study reported that AEFIs are a barrier to vaccine acceptance. It warrants the need to build trust in vaccines and the vaccination process. Transparent communication with the beneficiaries is crucial. AEFI monitoring and reporting should be an essential component of efforts to minimise vaccination hesitancy.Keywords: adverse effects following immunisation, vaccine hesitancy, parental perceptions, qualitative research